Facile and scalable engineering of a heterogeneous microstructure for uniform, stable and fast lithium plating/stripping. Issue 32 (2nd August 2019) - Wang, Xianshu; Zhuang, Jingchun; Liu, Mingzhu; Wang, Cun; Zhong, Yaotang; Wang, Huirong; Cheng, Xueqiong; Liu, Si; Cao, Guozhong; Li, Weishan
Abstract : Heterogeneous microstructure was engineered on Li electrode by solid-phase grinding reaction of Zn3 (PO4 )2 with Li metal. It presented high lithiophilicity and stability, providing Li metal anode with a uniform, stable and fast Li plating/stripping. Abstract : The uniform, stable and fast lithium (Li) plating/stripping, which enables a Li metal anode to be free from dendrites, is of great importance for the practical application of rechargeable Li metal batteries. Herein, a novel strategy was reported to provide the Li anode with a feature that involved engineering a heterogeneous microstructure on the Li metal via the solid-phase reaction between zinc phosphate and Li at room temperature. The as-engineered microstructure consisted of well-distributed LiZn and Li3 PO4 components, which possessed high Li-ion affinity and provided void spaces, enabling Li plating/stripping to be uniform, stable and fast. The resulting Li anode demonstrated cycling stability values of over 600, 210 and 140 h in an undecorated LiPF6 -based carbonate electrolyte for a symmetric cell at the current densities of 1, 3, and 5 mA cm −2, respectively, with low voltage hysteresis. Additionally, much better electrochemical performances of LiFePO4 full batteries could be obtained as compared to that of bare Li. This engineering is facile and scalable for the continuous manufacturing of Li anodes and therefore paves an avenue for the practical application of rechargeable high-energy-density Li metal batteries.